Serum biochemical parameters of female bronze Turkeys (Meleagris gallopavo) during egg-laying season - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos [UNESP]; Lapera, Ivan Moura [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; Nardi Junior, Leonildo [UNESP]; Testi, Alan Jonathan Pereira [UNESP] (My University, 2010)
Serum biochemical values of uric acid, urea, total proteins, albumin, globulin, Aspartate Aminotransferase (AST) and Gama Glutamiltransferase (GGT) were estimated in blood samples collected from 15 female Bronze Turkeys during the laying season (32-52 weeks of age). Significant differences were observed for total proteins, globulins, AST, urea and uric acid during the laying period evaluated. The major differences noted were due to elevations on total protein, globulins and uric acid concentrations in 52 week-old females. © Asian Network for Scientific Information, 2010.
Keywords: Bronze Turkey (Meleagris gallopavo); Laying season; Serum biochemical parameters; Meleagris gallopavo